Differential Diagnosis of Anemia in Patients with Rheumatoid Arthritis - Mykola VATUTIN,; Ganna SMYRNOVA,; Anna SHEVELYOK,; Olga KASHANSKA,; Olena SKLYANNA,; Olena KETING, (Archives of Rheumatology, 2014)
Objectives: This study aims to identify laboratory markers which can be used to distinguish between the different types of anemia in patients with rheumatoid arthritis (RA). Patients and methods: Ninety patients who met the American College of Rheumatology (ACR) criteria for RA and the World Health Organization (WHO) criteria for anemia were included in this study. We evaluated the hematocrit, color index, serum iron, ferritin, transferrin, and erythropoietin (EPO) levels along with the total iron binding capacity (TIBC) and mean erythrocyte volumes. Iron deficiency anemia (IDA) was defined as serum ferritin levels of <15 ng/ml) together with low serum iron levels (IDA group) while anemia of chronic disease (ACD) was defined as having serum ferritin levels of >15 ng/ml and normal serum iron levels (ACD group). Those with low serum iron and low/normal ferritin levels were included in the COMBI group, a combination of IDA and ACD (COMBI group). Results: The serum ferritin concentration was significantly increased and the serum transferrin level was significantly decreased in the IDA group compared with the ACD and COMBI groups. We also observed elevated EPO concentrations in all of the subgroups, but we found relative EPO deficiency only in the ACD and COMBI groups. Conclusion: Our findings suggest that the characte-ristics of COMBI anemia encompass the qualities of both ACD and IDA, particularly the latter. A differential diagnosis of anemia in patients with RA should be based on determining the serum iron and ferritin levels as well as the presence of relative EPO deficiency.